TAAT PAJAK DI JALAN RAYA: MENGUNGKAP DAMPAK PENGETAHUAN PERPAJAKAN DAN MODERNISASI ADMINISTRASI PADA WAJIB PAJAK KENDARAAN BERMOTOR - Khoirunnisak, Khoirunnisak; Utami, Endang Sri (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2024)
The adherence of motor vehicle taxpayers to tax regulations is a crucial matter in the context of augmenting local income. The objective of this study is to examine the impact of tax knowledge and the modernization of the tax administration system on taxpayer compliance at Samsat Gunungkidul. The research employed the multiple linear regression analysis technique on a sample of 100 taxpayers. The analysis results indicate that taxation awareness, Samsat Outlet, and Mobile Samsat have a substantial impact on taxpayer compliance; however, E-Posti does not have a significant effect. These findings suggest that it is crucial to enhance people's understanding of taxes and improve the efficiency of tax administration services in order to promote tax compliance. Local governments and key stakeholders should intensify their efforts to improve tax literacy, broaden the availability of tax services, and comprehensively assess the tax administration system. Therefore, by implementing measures to enhance tax compliance, we may effectively promote sustainable regional development.